Mu‘ḍilat al-aqlīyah al-Masīḥīyah fī ḥudūd balad al-sharī‘ah al-Islāmīyah - Miswari Miswari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
This article aims to find out the facts about the dilemmas faced by Christians as a minority in Aceh Tamiang regarding their desire to have houses of worship. All this while, Christians can only worship in their own houses. Indeed, their worship activities are always suspected and monitored by majority citizens, who are predominantly Muslim. The government and majority citizens are not at all concerned with the needs of Christian worship facilities. Actually, FKUB is a government institution that should be objective for this case, but they almost failed to defend for the needs of minorities. FKUB is only able to convey religious aspirations to government, but they have no power at all to deal with the case in the face of the regime. Rules made by the central government make difficulties for minority to establish their houses of worship. In addition, certain policies regulated by the Governor of Aceh have also contributed to create impossibility for Christian who would like to build their houses of worship. The sincere tolerance can only be realized by arousing the sympathy of the Muslims as the majority. They must be vehemently able to feel how if they are in position as minority.DOI: 10.15408/sdi.v25i2.6978